Розумні фабрики - Александрович, Д. П. (ХНУРЕ, 2021)
The paper considers the conditions of developing smart factories and finds the main principles used for their discovery. The analyses results say that the activity of smart factories is based on achievements of informational and automatic technologies, which allow to obtain new economical and technical effects in the production system and to get new efficiency. These principles are shown in the activity of Mariupol Iron and Steel Works named after Illich.
Keywords: розумні фабрики